Hubungan Tingkat Pengetahuan Ibu Hamil Tentang Anemia dengan Kejadian Anemia pada Ibu Hamil di Wilayah Puskesmas Cilacap Selatan I Kabupaten Cilacap Tahun 2025 - Nuryanti Nuryanti; Ima Syamrotul Muflihah (Pusat Riset dan Inovasi Nasional, 2025)
Anemia is a significant public health concern, particularly among pregnant women, as it can adversely affect both maternal and fetal health. During pregnancy, the body’s iron requirements increase due to the demands of the growing fetus and the increased blood volume in the mother. Iron deficiency anemia (IDA) is the most common type of anemia among pregnant women, and it can lead to complications such as preterm birth, low birth weight, and maternal morbidity. Adequate iron intake is crucial for preventing anemia, and adherence to iron supplementation is essential for managing and preventing this condition. Knowledge of anemia, including its causes, consequences, and prevention methods, is a key factor influencing the adherence to iron tablet consumption among pregnant women. Women with better knowledge are more likely to understand the importance of iron supplementation and are more consistent in taking their prescribed iron tablets. In contrast, those with limited knowledge may fail to recognize the significance of proper nutrition and the necessity of adhering to medical recommendations. Health education interventions have been shown to improve maternal knowledge about anemia and, in turn, enhance compliance with iron supplementation regimens. The findings of this study underscore the relationship between maternal knowledge and the occurrence of anemia during pregnancy. It was found that women with good knowledge about anemia had a lower incidence of the condition. This emphasizes the need for health education programs at the community level to enhance awareness and promote the importance of iron supplementation. Health professionals should focus on educating pregnant women about the risks of anemia, the benefits of iron tablets, and the proper consumption methods to reduce the prevalence of anemia and improve maternal and fetal health outcomes.